CARBON DIOXIDE REMOVAL FROM EXHAUST GASES OF METHANE COMBUSTION BY AMINE MODIFIED MCM - 41 - Ramazan Ali Dianati Tilaki; Fatemeh Norouzi (Journal of Air Pollution and Health, 2017)
Introduction: Large amount of CO2 emissions from combustion of fossil fuels will lead to environmental crisis. One method for removing CO2 is adsorption by modified adsorbents. In this study, mesoporous silica, MCM- 41, modified by mono- ethanolamine, was used for CO2 removal from exhaust gases of methane combustion. Materials and methods: MCM- 41 was synthesized by using tetraethyl orthosilicate (TEOS) as silica source, according to classic method. MCM- 41 was modified with different amounts (25, 50 and 75 %) of monoethanol amine (MEA) by impregnation method. Amine modified MCM- 41 were used in filters and adsorption experiments were conducted to determine adsorption capacity by passing CO2 in different concentrations (2000 -5000 ppm), different flow rates (100 – 400 ml/min), and different temperatures (25, 55 and 90 °C) individually. CO2 was analyzed by ND IR CO2 analyzer. Results: Time to reach adsorption equilibrium of carbon dioxide on to examined adsorbents was about 10 h. Maximum carbon dioxide adsorption capacity for MCM- 41 was determined 5.0 mg/g. Maximum adsorption rate was due to MCM41- MEA 50 % with adsorption capacity of 50 mg/g for CO2 concentration of 5000 ppm. By increasing temperature from 25 to 90 °C, adsorption capacity was increased only about 10 %. Maximum CO2 adsorption capacity was achieved at gas flow rate of 100 mL/min, and by increasing flow rate, capacity was decreased. By increasing amine loaded on MCM, CO2 adsorption capacity was decreased. Conclusions: Modification of MCM- 41 using monoethanol amine by simple impregnation method will result in the production of adsorbents with a higher absorption capacity for carbon dioxide removal. By using amine modified MCM- 41, it is possible to remove carbon dioxide from exhaust gases of methane combustion.